2018
DOI: 10.17705/1jais.00495
|View full text |Cite
|
Sign up to set email alerts
|

Design Science Research Contributions: Finding a Balance between Artifact and Theory

Abstract: With the rising interest in Design Science Research (DSR), it is crucial to engage in the ongoing debate on what constitutes an acceptable contribution for publishing DSR -the design artifact, the design theory, or both. In this editorial, we provide some constructive guidance across different positioning statements with actionable recommendations for DSR authors and reviewers. We expect this editorial to serve as a foundational step towards clarifying misconceptions about DSR contributions and to pave the way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
185
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(222 citation statements)
references
References 44 publications
4
185
1
3
Order By: Relevance
“…Leading scholars in the field of design science research have called for more research on the actual design of novel and useful artifacts (Baskerville et al 2018;Peffers et al 2018). A particularly interesting form of design artifacts are cyberphysical systems, which are expected to greatly enhance previously non-digitized systems by providing ''new use that was previously inaccessible'' through tight integration and coordination between physical and digital resources (Brandt et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Leading scholars in the field of design science research have called for more research on the actual design of novel and useful artifacts (Baskerville et al 2018;Peffers et al 2018). A particularly interesting form of design artifacts are cyberphysical systems, which are expected to greatly enhance previously non-digitized systems by providing ''new use that was previously inaccessible'' through tight integration and coordination between physical and digital resources (Brandt et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The literature review has shown that there is an identifiable business value in having such an artifact. In DSR, the practical utility embodies a central role, ensuring research relevance [10,3]. On the other side, DSR employs the academic knowledge base of existing theories, models, and frameworks to build the artifact.…”
Section: Methodsmentioning
confidence: 99%
“…framework clusters contributions according to the maturity of both the application domain and the solution. We argue that the proposed artifact provides a novel solution to a known problem [3]. The literature research reveals no evidence that banks have yet employed location-based customer prediction systems to this date.…”
mentioning
confidence: 91%
“…ADR is a combined method of AR and DSR. AR itself is a change-oriented approach, with which social processes can be studied by researcher guided changes, of which effects are then monitored (Baskerville et al, 2018). DSR combines behavioral science and design science and adds rigor and theory to the design of artifacts (Hevner et al, 2004).…”
Section: Action Design Researchmentioning
confidence: 99%